Transoral Endoscopic Vestibular Thyroglossal Duct Cyst Excision. (December 2020) - Ryan, Marisa A.; Russell, Jonathon O.; Schoo, Desi P.; Upchurch, Patrick A.; Walsh, Jonathan M.
Objective: Thyroglossal duct cysts (TGDCs) are relatively common congenital midline neck masses that are treated with surgical excision. Traditionally these are removed along with any associated tract and the central portion of the hyoid bone through an anterior neck incision. Some patients with TGDCs want to avoid an external neck scar. Methods: We describe the details of a transoral endoscopic vestibular excision of a TGDC and the associated hyoid bone in an adolescent patient. Results: This novel approach was successful and there were no complications. Conclusion: We propose that cervical TGDCs can be safely and completely removed with this approach in appropriately selected patients while avoiding a neck scar.